Water Resource Management Discourse in Indonesia (Case Studi 2002-2015) - Agus Susilo, Dwi; Sarwoprasodjo, Sarwititi; Hubeis, Musa; Ginting, Basita (Sodality: Jurnal Sosiologi Pedesaan, 2016)
ABSTRACTThe discourse of water resources management that occurred in Indonesia for more than a decade involving governments and civil society be interesting to watch. The purpose of this study is to interpret and analyze the discourse and argumentation conflicting parties in the public sphere in water resource management in Indonesia in 2002-2015. Benefits of theoretical research is to increase the variety of discourse analysis method. This critical research paradigm using the theory of Communicative Action Habermas who developed the concept of discourse. Using the method of DHA Wodak as a method of discourse rooted in the critical theory of Habermas researchers managed to see the interests behind the making of Law No. 7 of 2004 on Water Resources and arguments used to use legal rationality and everyday language. Water Resources Law 2004 born of global importance that took the interests of katas ha of water and water privatization. Through discourse with distortion-free communication, guarantees the rationality, where the best reliable arguments to challenge oppressive power and hegemonic ideology.Keywords: argumentation, critique, discourse, privatization, public sphere, water rightABSTRAKDiskursus pengelolaan sumber daya air yang terjadi di Indonesia lebih dari satu dekade yang melibatkan pemerintah dan masyarakat sipil menarik untuk diamati. Tujuan penelitian ini adalah menafsirkan dan menganalisis diskursus dan argumentasi pihak-pihak yang berkonflik di ruang publik dalam pengelolaan sumber daya air di Indonesia tahun 2002-2015. Manfaat penelitian secara teoretis adalah untuk menambah variasi   metode analisis diskursus. Penelitian berparadigma kritis ini menggunakan teori Tindakan Komunkatif Habermas yang mengembangkan konsep diskursus. Menggunakan metode DHA Wodak sebagai metode diskursus yang berakar pada teori kritis Habermas peneliti berhasil melihat kepentingan di balik pembuatan UU Nomor 7 Tahun 2004 tentang Sumber Daya Air dan argumentasi yang digunakan menggunakan rasionalitas hukum dan bahasa sehari-hari. UU SDA lahir dari kepentingan global yang membawa kepentingan hak atas air dan privatisasi air. Melalui diskursus dengan komunikasi bebas distorsi menjamin lahirnya rasionalitas, dimana argumentasi terbaik dapat diandalkan untuk menantang kekuasaan yang menindas dan ideologi yang hegemonik.Kata kunci: argumentasi, kritik, diskursus, privatisasi, ruang publik, hak atas air